Psychodrama’s Role in Alleviating Acute Distress: A Case Study of an Open Therapy Group in a Psychiatric Inpatient Ward - Ron, Yiftach (Frontiers in Psychology, 2018)
Numerous studies point to the acute distress associated with experiencing severe mental illness and psychiatric hospitalization. Another strand of research describes how the unique features of psychodrama group therapy are useful in fostering spontaneity and creativity, and their benefits in treating particularly difficult populations where traditional psychotherapy is limited. This paper provides a framework for understanding the potential of psychodrama group therapy to alleviate the experience of loneliness and distress in psychiatric inpatients. A case study of an open inpatients psychodrama group in a psychiatric hospital in Israel demonstrates the role of therapeutic means such as the doubling technique and group sharing phase in creating and reinforcing empathy, relatedness, and support, which may offer at least partial relief of the distress and loneliness of psychiatric inpatients. The unique contribution of this study is the intimate encounter that it provides to researchers and practitioners with the processes that take place within the setting of inpatients therapy group.